2013
DOI: 10.5812/atr.12501
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Ischemia and Reperfusion Injury and Trauma: Current Concepts

Abstract: ContextIschemia-reperfusion injury is a fascinating topic which has drawn a lot of interest in the last several years. Hepatic ischemia reperfusion injury may occur in a variety of clinical situations. These include transplantation, liver resection, trauma, and vascular surgery.Evidence AcquisitionThe purpose of this review was to outline the molecular mechanisms underlying hepatic I/R injury and present the latest approaches, both surgical and pharmacological, regarding the prevention of it. A comprehensive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 74 publications
0
46
0
3
Order By: Relevance
“…Oxidative stress also plays a prominent role in IRI, presumably through ischemic inhibition of mitochondrial SDH activity, which leads to disruption of electron transport during reperfusion and the generation of ROS (Papadopoulos et al, 2013;Chouchani et al, 2014). Accordingly, we found that 2-ACP injected prior to the reperfusion phase (Fig.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Oxidative stress also plays a prominent role in IRI, presumably through ischemic inhibition of mitochondrial SDH activity, which leads to disruption of electron transport during reperfusion and the generation of ROS (Papadopoulos et al, 2013;Chouchani et al, 2014). Accordingly, we found that 2-ACP injected prior to the reperfusion phase (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Based on this pathogenic complexity, it has been difficult to identify primary mediators or mechanisms that might be relevant therapeutic targets. Nonetheless, oxidative stress appears to be a significant component of IRI (Papadopoulos et al, 2013), and the use of antioxidant compounds that decrease cellular levels of reactive oxygen species (ROS) is an obvious pharmacotherapeutic strategy. However, clinical trials provided only mixed support for antioxidant therapy (Jaeschke and Woolbright, 2012;Papadopoulos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic portal occlusion can cause hepatic ischemia and hypoxia, therefore it may affect the synthesis of mitochondrial energy and electron transport in the respiratory chain (16,17), producing numerous oxygen free radicals, which cause cell damage via lipid peroxidation of biological membranes (18). Lipid peroxidation itself produces toxic substances, including MDA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, activation of Kupffer cells and neutrophils leads to the release of inflammatory cytokines cascades and free radicals that damage the liver severely (42).…”
Section: Discussionmentioning
confidence: 99%